Resilient dissipative dynamic output feedback control for uncertain Markov jump Lur'e systems with time-varying delays. (May 2017) - Zhang, Yujie; Ou, Yongsheng; Wu, Xinyu; Zhou, Yimin
Abstract: The resilient dissipative dynamic output feedback control problem for a class of uncertain Markov jump Lur'e systems with piecewise homogeneous transition probabilities and time-varying delays in the discrete-time domain are examined in this study. The designed controller can tolerate additive uncertainties in the controller gain matrix, which result from controller implementations. The time-varying delays are also supposed to be mode-dependent with lower and upper bounds known a priori . By constructing a Lyapunov–Krasovskii functional candidate, the sufficient conditions regarding the existence of desired resilient dissipative controllers are obtained in terms of linear matrix inequalities, thereby ensuring that the resulting closed-loop system is stochastically stable and strictly dissipative. Two numerical examples were established to illustrate the effectiveness of the proposed theoretical results.